Surgeon heart rate analysis during the dental implant procedure - Paulo Roberto Silva Câmara; Mateus Bertolini Fernandes Santos; Jarbas Francisco Fernandes Santos; Vicente de Paula Prisco Cunha; Leonardo Marchini (Universidade Estadual de Campinas, 2016)
Dental implant placement is a singular procedure in dentistry, and many variables should influence its success. The operator's attitudes during surgeries are some of these variables. Considering that, the present paper aims to evaluate surgeon's stress during different stages of dental implant placement. The heart rates of ten post-graduate students of implantology were evaluated at rest and during various steps of the implant placement procedure, using a Pollar R device. Each surgeon's heart rate was monitored at different moments (preparation of the surgery; anaesthesia; incising and flapping procedures; bone perforating; implant placement at bone site; suture; end of the surgical procedure) during a single surgical implant insertion procedure (without additional procedures such as expansion, grafting and others). Implantodontic interventions were found to be the most stressful of these procedures, and implant placement in the bone site the most critical. Current procedures for the general practitioner, such as local anaesthesia, induced minor variations in the heart rate and, hence, less stress.